Magnetic and Spectroscopic Studies of the Synthesized Metal Complexes of Bis(Pyridine-2-carbo) Hydrazide and Their Antimicrobial Studies - Netra Pal Singh; Anu; Jagvir Singh (E-Journal of Chemistry)
Cobalt(II), Nickel(II), Copper(II) and Manganese(II) complexes, having the general composition {M(L)2X2}, have been synthesized [where L= bis(pyridine-2-carbo) hydrazide(L), and X = Cl–]. All the Metal complexes reported here have been characterized by elemental analysis, molar conductance, magnetic moments, IR, electronic and mass spectral studies. All the complexes were found to have magnetic moments corresponding to unpaired electrons. The possible geometries of the complexes were assigned on the basis of electronic and infrared spectral studies. On the basis of molar conductance values the complexes show 1:2 electrolytic nature. Newly synthesized ligand and its Metal complexes have been screened against Staphylococcus aureus (ATCC 25923), Staphylococcus aureus (ATCC 3160) bacterial species and Candida albicans (227) and Staphylococcus cereviscae (361) fungal species.